V1/V2 Neutralizing Epitope is Conserved in Divergent Non-M Groups of HIV-1. (1st March 2016) - Morgand, Marion; Bouvin-Pley, Mélanie; Plantier, Jean-Christophe; Moreau, Alain; Alessandri, Elodie; Simon, François; Pace, Craig S.; Pancera, Marie; Ho, David D.; Poignard, Pascal; Bjorkman, Pamela J.; Mouquet, Hugo; et al.
Abstract : Background: Highly potent broadly neutralizing monoclonal antibodies (bNAbs) have been obtained from individuals infected by HIV-1 group M variants. We analyzed the cross-group neutralization potency of these bNAbs toward non-M primary isolates (PI). Material and Methods: The sensitivity to neutralization was analyzed in a neutralization assay using TZM-bl cells. Twenty-three bNAbs were used, including reagents targeting the CD4-binding site, the N160 glycan-V1/V2 site, the N332 glycan-V3 site, the membrane proximal external region of gp41, and complex epitopes spanning both env subunits. Two bispecific antibodies that combine the inhibitory activity of an anti-CD4 with that of PG9 or PG16 bNAbs were included in the study (PG9-iMab and PG16-iMab). Results: Cross-group neutralization was observed only with the bNAbs targeting the N160 glycan-V1/V2 site. Four group O PIs, 1 group N PI, and the group P PI were neutralized by PG9 and/or PG16 or PGT145 at low concentrations (0.04–9.39 μg/mL). None of the non-M PIs was neutralized by the bNAbs targeting other regions at the highest concentration tested, except 10E8 that neutralized weakly 2 group N PIs and 35O22 that neutralized 1 group O PI. The bispecific bNAbs neutralized very efficiently all the non-M PIs with IC50 below 1 μg/mL, except 2 group O strains. Conclusion: The N160 glycan-V1/V2 site is the most conserved neutralizing site within the 4 groups of HIV-1. This makes it an interesting target for the development of HIV vaccine immunogens. The corresponding bNAbs may be useful for immunotherapeutic strategies in patients infected by non-M variants. Abstract : Supplemental Digital Content is Available in the Text.